Progressive disseminated histoplasmosis presenting like chronic parenchymal liver disease with ascites: a rare case report and discussion - Banerjee, Arnab (International Journal of Research in Medical Sciences, 2017)
A 82 year old diabetic and hypertensive Muslim man presented with ascites along with features of portal hypertension. Though it initially seemed to be a primary case of chronic parenchymal liver disease, investigations revealed it to be a case of Progressive Disseminated Histoplasmosis (PDH) with bilateral adrenomegaly, hepatosplenomegaly and ascites. The ascites was high SAAG in nature and no evidence of malignancy or tuberculosis could be found. The patient was treated with liposomal amphotericin B and was subsequently discharged on oral itraconazole therapy. On follow-up he was found to be significantly better at 3 months.